2021
DOI: 10.1007/s11547-021-01338-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on workload burden of a complex radiotherapy facility

Abstract: Background and purpose COVID-19 constitutes a worldwide threat, prompting Italian Government to implement specific measures on March 8, 2020, to protect patients and health workers from disease transmission. The impact of preventive measures on daily activity of a radiotherapy facility may hamper the ability to fulfill normal workload burden. Thus, we assessed the number of delivered treatments in a specific observation period after the adoption of preventive measures (since March 11 to April 24,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…These findings seem to suggest that SSRT may be considered a valid alternative for post-prostatectomy macroscopic local recurrence, offering short (convenient), cost-effective, well-tolerated and efficacious approach. Interestingly, shorter treatment schedule may be particularly useful during the COVID-19 pandemic [ 25 , 26 ]. Moreover, SSRT may offer a valid approach to implement information offered by new imaging modalities (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These findings seem to suggest that SSRT may be considered a valid alternative for post-prostatectomy macroscopic local recurrence, offering short (convenient), cost-effective, well-tolerated and efficacious approach. Interestingly, shorter treatment schedule may be particularly useful during the COVID-19 pandemic [ 25 , 26 ]. Moreover, SSRT may offer a valid approach to implement information offered by new imaging modalities (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…As to the “gravity assessment” of COVID-19 infection and evaluation of pulmonary parenchymal involvement, several scores have been proposed [ 62 , 63 ]. The main goal of these tools is to establish a well-defined strategy for evaluation of the airways and lungs of COVID-19 positive patients from Computed Tomography (CT) scans, including detected abnormalities [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. Their identification and the volumetric quantification may allow an easier classification in terms of gravity, extent and progression of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of organizational well-being, the high score reported for each ITEM showed that the organizational changes during COVID-19 period were well tolerated due to the knowledge of their utility in terms of patients and personal security. Another analysis, despite without the use of an organizational well-being questionnaire, showed the same results; in fact, Francolini et al showed that organizational changes during pandemic did not significantly affect normal radiotherapy workflow in selected situations [ 24 ].…”
Section: Discussionmentioning
confidence: 75%